1999
DOI: 10.1108/09540919910293856
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of underfill encapsulants for flip‐chip technology

Abstract: This paper presents results on adding silane coupling agents to the underfill encapsulant to enhance the rheology and wetting of the underfill. These results include rheology measurements, contact angle measurements, and in situ flows using a simulated test chip on an FR4 with solder mask substrate. Three properties of the underfill encapsulant that can affect the mechanical reliability of the die and substrate assembly are: CTE; elastic modulus; and adhesion to the die and substrate surfaces. The approach tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In addition, studies [18], [19] suggested that the local viscosity variation in suspensions induced by shear migration (the particle motion across the streamlines by irreversible particle interactions) becomes negligible with the decrease of the filler particle size. In this paper, Underfill A has a mean diameter of 0.3 µm, much smaller than that of most previous underfill studies whose filler particles are several micrometers in diameter [1]- [4], [10]- [12], [17]- [19]. Fig.…”
Section: A Viscositymentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, studies [18], [19] suggested that the local viscosity variation in suspensions induced by shear migration (the particle motion across the streamlines by irreversible particle interactions) becomes negligible with the decrease of the filler particle size. In this paper, Underfill A has a mean diameter of 0.3 µm, much smaller than that of most previous underfill studies whose filler particles are several micrometers in diameter [1]- [4], [10]- [12], [17]- [19]. Fig.…”
Section: A Viscositymentioning
confidence: 97%
“…In order to redistribute the thermal stresses induced by the mismatch in the coefficient of thermal expansion among a silicon die, solder joints, and a substrate, underfill material is used to fill the gap containing thousands of bump interconnects between the die and substrate [1], [2]. The underfill material, a liquid encapsulant consisting of mostly epoxy resin and SiO 2 filler particles, is usually dispensed along a silicon die edge and flows through the multiply-connected gap region by capillary action.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier days of flip chip technology, the chip was mounted onto the ceramic substrates and as the chip size was relatively small, the CTE mismatch between chip and substrate was not sufficient enough to cause reliability issue [4]. Since the late 1980s, the chip has been increasing in size to meet the growing demand on high performance of I/O.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the ceramic substrate was replaced by organic substrate because it is not able to adequately support the growing I/O counts due to its inherent limitation in thermal cycling reliability, density, and cost of use [5]. However, the use of organic substrate such as FR4 and polyimide has imposed significant thermal stresses on solder joints during thermal loading due to the greater difference in CTE between the chip and organic substrate [4,5]. Thus, the thermo-mechanical stress on solder joints became the cause of common failure of flip-chip package as the stress is induced to the interconnections repeatedly under cyclic thermal loading environment.…”
Section: Introductionmentioning
confidence: 99%
“…Since silicon nitride (Si 3 N 4 ) has the high dielectric constant, the complex insulated layer composed of Si 3 N 4 /benzocyclobutenone (BCBO) has a larger unit capacitance and smaller leakage current. [16][17][18][19][20][21][22][23][24] First, a film of 8 nm p-6P was deposited on the insulator, forming discontinuous islands when the substrate temperature was kept at 180 C, which is used to induce the growth of continuous polycrystalline rubrene thin films with large grains. Subsequently, the substrate temperature was dropped to 100 C, and the film of 20 nm rubrene was deposited on p-6P.…”
mentioning
confidence: 99%